Families of Immigrant Origin in a Situation of Chronicity in Social Services. An Approach to Their Reality and Minors’ Expectations Based on the Parents’ Discourse - Julià Traveria, Ramon; Miranda Ruche, Xavier; Pirla Santamaria, Alba (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
Families of immigrant origin with minors are one of the profiles likely to enter a situation of chronicity and dependence on social services. They are also at risk of intergenerational transmission of poverty. In this article we start from an intentional sample of twenty-seven families in a situation of chronicity in order to develop an analysis of the discourses of the parents. The objective is to provide knowledge regarding their reality and social context. The results have been structured in three areas: relationships with social services, the internal strengths of families, and finally, the projections about the future of their children. In terms of implications for intervention, we point out the positive remnant that appears in parents' discourse in terms of expectations for change. However, this should be accompanied by more economic and technical resources to reduce the social risk factors to which families and their children are exposed.
Keywords: social services; chronicity; immigrant families; minors; vulnerability